Experiences of Communication Challenges in the Workplace and Pathways to Career Continuation for Novice Nurses - Umemoto, Tomoko; Sakamoto, Mayu; Kawamura, Namiko (Journal of Japan Academy of Nursing Science, 2025)
Objective: The aim was to elucidate the pathways and experiences of novice nurses who choose to continue working despite experiencing communication difficulties in the workplace.Methods: Semi-structured interviews were conducted with five novice nurses. Themes were extracted using phenomenological methods and were subsequently used to model the process through Trajectory Equifinality Modeling.Results: From the interviews, four thematic stages were identified: (1) Frustration and distress from being unable to demonstrate one’s worth to senior nurses, (2) Putting on a brave front, (3) Struggling to find one’s ideal nursing practice despite inadequate job performance, and (4) Achieving growth as a ‘nurse’.Conclusion: Novice nurses experience communication difficulties with senior members of staff and through incidents and interactions with their peers, recognize their own growth, interpersonal relationships, and support from their environment. This recognition leads to a renewed motivation for growth and the choice to continue in their profession. This process can be considered as the emergence of ‘self-transformation’.